ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN NELAYAN TANGKAP PANCING RAWAI KELURAHAN SUMPANG BINANGAE KACAMATAN BARRU - abdul hafid; ilham abu (Fakultas Ekonomi Universitas Indonesia Timur, 2019)
Working as a fisherman is a job that has a fairly high level of risk. In addition, the income received from fish catches is not fully able to meet the economic needs of his family. There are many factors that can cause fishermen income such as capital, fishing gear, fishing time and other factors. The purpose of this study was to analyze the factors that influence the income of Rawai fishing in the Sumpang Binagae Village in Barru regency. The method used in this research is quantitative descriptive. The population in this study were 46 family heads of fishermen in Sumpang Binangae Village. Data collection techniques through observation, documentation, interviews and questionnaires while the data analysis technique used is multiple regression analysis. The results showed that the size of the income of fishermen who use fishing gear significantly and significantly influenced by the variable working capital, fishing gear, length of sea fishing and experience while the dependent variables of family, education and age did not significantly influence the income of fishermen. Income for longline fishing has a good income level due to the type of fish catches that have economic value or higher selling prices.